The importance of institutional support in the implementation of protocols and care flows in primary health care in municipalities in the state of amapa: experience report - do Socorro Matos Pantoja, Cintia; Lieverson Nogueira do Carmo, Weslley; da Silva Purity, Nilma; Farias da Costa, Donato; Nunes dos Santos, Doriane; Amoras Távora, Juvanete (Seven Editora, 2023)
The Assistance Protocols and Flows in the work routine are important to face problems in assistance and in the management of services. These instruments are guided by clinical and organizational guidelines and are based and validated by studies and scientific evidence, in addition to incorporating new technologies into services. In this aspect, aiming at the organization of the Health Care Networks in the State of Amapá, specifically at this moment the Maternal and Child Care Network, the Care Network for People with Chronic Non-Communicable Diseases and the Urgency and Emergency Network, it was observed during the accomplishment of a Situational Diagnosis the need to implement Protocols and Assistance Flows, as well as the accomplishment of in-service training for the health professionals of the cities of Laranjal do Jari, Vitória do Jari, Oiapoque, Cutias do Araguari and Amapá, thus aiming qualification in the assistance provided to users of the Unified Health System and the strengthening of the referred networks in the State. The research is descriptive with a qualitative approach of the Experience Report type. The period of carrying out the activities in the municipalities took place during the year 2021, from March to December and the beginning of the year 2022 from March to April. It is important to highlight that the state institutional support process was established with the development of actions and activities through the use of active methodologies, delivery of guiding documents, presentation of proposals for Assistance Flows and Protocols and realistic in-service training, aiming at optimizing and qualification in clinical and care management, in addition to improving health indicators and strengthening Health Care Networks. DOI: 10.56238/pacfdnsv1-039